Conspicuous and cryptic morphs of a polytypic poison frog differ in reproductive output because of differences in tadpole performance, not parental effort. Issue 4 (1st October 2016) - Dugas, M.B.; Richards-Zawacki, C.L.
Abstract : Predation risk can drive life-history evolution in prey, with high adult mortality favouring the prioritization of current over future reproduction. Populations that evolve or adopt different or differently effective strategies to avoid predation, then, should evolve different life-history strategies. We compared reproductive output, under identical captive breeding conditions, of three allopatric morphs of polytypic poison frog ( Oophaga pumilio ) that likely experience different predation risk. We predicted that pairs of a well-defended (conspicuous and highly toxic) morph would prioritize future reproduction, and thus reproduce less often than a poorly defended (cryptic and less toxic) morph, while a cryptic but highly toxic lineage would be intermediate. These predictions were generally met: the conspicuous, toxic morph produced fewer juveniles than the cryptic morphs. However, the results of cross-fostering tadpoles among morphs suggested that these differences arose not from the quality of care parents provided, as predicted by life-history theory, but rather from differences expressed in tadpoles. Moreover, all cross-fostered tadpoles were less successful than tadpoles reared by their own parents, perhaps suggesting that parents discriminate against unrelated tadpoles or that parental care and offspring solicitation behaviours have diverged among populations. These results suggest opportunities for comparative studies exploring the entire complexity of the selective landscapes experienced by these polytypic frogs.